EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH COUNTER PRESSURE MASSAGE TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF (Jurnal Kesehatan Siliwangi, 2022)
Background : Pain in the active phase of labor in the first stage can affect the increase in blood pressure and fetal heart rate, and interfere with the mother's concentration during labor. The initial peak of pain usually occurs when labor enters the active phase. One of the non-pharmacological methods in reducing the intensity of labor pain is massage or massage in the form of counter pressure. Counterpressure massage is able to make endorphin compounds active so that they can inhibit the transmission of pain to reduce pain intensity. Purpose : The purpose of this Evidence Based Case Report is to determine differences in pain intensity during the first active phase of labor before and after application of counterpressure massage. Method : A search for articles regarding the effect of counterpressure massage was carried out on the Scholar e-database and the Garuda Portal. From the search results, it was found that two articles with a quasi-experimental research design by M. Satria and Nurfaizah, et al were filtered based on criteria and reviewed critically. Measurement of pain intensity was carried out before and after administering Counterpressure massage using the Numeric Rating Scale (NRS) and the result was that there was a decrease in pain scores. Result : The intensity of pain before being given Counterpressure massage obtained a value of 5 (moderate pain) while after being given Counterpressure massage obtained a value of 3 (mild pain). Conclusion : Counterpressure massage for labor pain is effective in reducing labor pain.